2004
DOI: 10.1080/10739680490278592
|View full text |Cite
|
Sign up to set email alerts
|

The Perfusion Paradox and Vascular Instability in Sickle Cell Disease

Abstract: Sickle cell disease (SCD) exhibits a curious coexistence of contrasting perfusion profiles in the circulatory system: hypoperfusion is endemic in microcirculatory beds occluded by hemoglobin S-containing erythrocytes while hyperperfusion characterizes the systemic (macro)circulation and a number of regional vascular circuits. This review highlights this perfusion paradox of SCD, focusing on forearm blood flow and the renal circulation, and exploring the extent to which alterations in vasoactive systems (such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 119 publications
(193 reference statements)
4
68
0
1
Order By: Relevance
“…In view of the marked increase in blood flow that occurred in wild-type mice following the creation of an AVF, we posited that a disease that exhibits impaired hemodynamic responses would fail to mount the expected increase in AVF flow and preservation of AVF function. The rheologic abnormalities in SCD have long been recognized (11,25), and our prior studies demonstrated that the vasculature in a transgenic murine model of SCD exhibits impairment in endothelium-dependent and endothelium-independent vasorelaxant responses (26). We thus employed this murine model as a representative disease to test this hypothesis.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In view of the marked increase in blood flow that occurred in wild-type mice following the creation of an AVF, we posited that a disease that exhibits impaired hemodynamic responses would fail to mount the expected increase in AVF flow and preservation of AVF function. The rheologic abnormalities in SCD have long been recognized (11,25), and our prior studies demonstrated that the vasculature in a transgenic murine model of SCD exhibits impairment in endothelium-dependent and endothelium-independent vasorelaxant responses (26). We thus employed this murine model as a representative disease to test this hypothesis.…”
Section: Resultsmentioning
confidence: 88%
“…We next sought to determine the contribution of a vasorelaxant system, specifically, heme oxygenase-1 (HO-1), in enabling the augmented blood flow that occurs in the AVF. Finally, to examine whether AVF flow and function would be compromised in a representative disease attended by impaired hemodynamic responses, AVF blood flow and patency were assessed in a murine disease model in which critical aspects of hemodynamic responses (vasorelaxation and blood rheology) are known to be substantially perturbed (11,25,26).…”
mentioning
confidence: 99%
“…It has been reported that this may be a consequence of important haemorheological mechanisms such as the Fahraeus-Lindquist effect. [7][8][9] Moreover, marginal variations may exist between the recorded values and actual microcirculatory oxygen delivery, as all viscosity studies, including the present study, have used samples taken from venous blood and then extrapolation made regarding delivery to tissues.…”
Section: Discussionmentioning
confidence: 99%
“…56,56b,60 As such, plasma hemoglobin-free and oxygen-free radical-mediated consumption of nitric oxide produces a state of resistance to nitric oxide in patients with sickle cell disease. 56,58,[61][62][63][64][65] Downstream effects of hemolytic anemia include increased endothelin-1 expression, hememediated and free iron-mediated oxygen radical generation, platelet activation, and increased endothelial adhesion molecule expression. 4,56,[66][67][68] In patients with sickle cell disease, plasma endothelin-1 levels are increased in steady state and during crisis.…”
Section: Hemolysismentioning
confidence: 99%